Improved ferroelectric, piezoelectric, and dielectric properties in pure KNN translucent ceramics by optimizing the normal sintering method. Issue 14 (15th July 2022) - Rahman, Attaur; Jiang, Minhong; Rao, Guanghui; Lee, Soonil; Kim, Myong-Ho; Habib, Muhammad; Rahman, Jamil Ur
Abstract: In this study, it is reported that various properties can be selectively derived in a pure (K0.5 Na0.5 )NbO3, KNN ceramics through optimizing the sintering temperature by the conventional sintering method. High piezoelectric, ferroelectric, and dielectric properties such as d 33  = 127 pC/N, P r  = 31 μC/cm 2, and ε r  = 767 are obtained at the sintering temperature of 1100 °C. On the contrary, the specimen sintered at 1130 °C does not show high piezoelectric and ferroelectric properties, but it is translucent with a transmittance of 22% and 57% at the wavelength of 800 and 1600 nm respectively and shows a very high dielectric constant ε r of 881. The origin of the high piezoelectric constant owes to large remanent polarization and dielectric constant, and dense microstructure with uniform distribution of large grains with the conjunction of relatively large crystal anisotropy. On the other hand, dense microstructure with almost no porosity, highly compacted grain boundaries, uniform distribution of grains, and relatively low crystalline anisotropy are responsible for the translucency and large dielectric constant of the ceramic specimens. This study demonstrates that the lead-free KNN ceramic has the potential to show multiple noteworthy properties such as piezoelectric, ferroelectric, dielectric, and transparent properties. This work provides a pure KNN ceramic simultaneously with high piezoelectric and transparent characteristics prepared only by using the conventional sintering method at a moderate sintering temperature for the first time in the literature.